Carbon and nitrogen concentrations alongside stable isotopes of the sediment core segment EN20001_6 from Lake Khamra, Yakutia, Siberia - Amelie Stieg; Mikaela Weiner; Jens Strauss; Justin Lindemann; Boris K Biskaborn; Ulrike Herzschuh; Izabella Baisheva; Luidmila A Pestryakova; Hanno Meyer (PANGAEA, 2025)
The data contains biogeochemical data, including total carbon and nitrogen concentrations, as well as stable carbon (δ13C) and nitrogen isotopes (δ15N) of 21 samples from the core segment EN20001_6. All measurements were carried out at AWI Potsdam. TOC was analysed by using an Elementar soli TOC cube, whereas TN was quantified by an Elementar rapid MAX N exceed. The measurement accuracy was 0.1 % for both devices. We computed the total carbon (TC) by the sum of TOC and the total inorganic carbon (TIC). Furthermore, we calculated the TOC/TN atomic ratio by multiplying its mass ratio by 1.167, which is the ratio of the atomic weights of nitrogen and carbon (Meyers and Teranes, 2001). Carbon and nitrogen isotopes (δ13C,δ15N) were determined using a ThermoFisher Scientific Delta-V-Advantage gas-mass spectrometer equipped with a FLASH elemental analyser EA 2000 and a CONFLO IV gas-mixing system and an MA200R autosampler system at ISOLAB of AWI Potsdam. We removed inorganic carbon by a hydrochloric acid treatment (HCl, 1.3 mol L-1) prior carbon isotope. Isotope ratios are given relative to laboratory standards of known isotopic compositions relative to the Vienna Pee Dee Belemnite (VPDB) reference standard for carbon and to the standard atmospheric nitrogen ratio (air) for nitrogen. Results are given as delta notation (δ13C, δ15N) in per mill ( extperthousand), with 1σ standard error better than ±0.15 extperthousand.